2014
DOI: 10.1021/ac403195f
|View full text |Cite
|
Sign up to set email alerts
|

d-α-tocopheryl Polyethylene Glycol 1000 Succinate: A View from FTICR MS and Tandem MS

Abstract: D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) is an important polymeric excipient frequently used in drug formulation. However, differing compositions of the TPGS samples between batches are believed to result in variable performance of the formulated product. Herein, a high performance method using Fourier-transform ion cyclotron resonance (FTICR) mass spectrometry (MS) and tandem mass spectrometry (MS/MS) to analyze the composition of TPGS samples and the structure of TPGS was established. Aided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 35 publications
(59 reference statements)
1
27
0
Order By: Relevance
“…In EID, ions are irradiated with fast electrons (6-20 eV) in order to induce electronic excitation, form radical specials, and initiate dissociation. EID is usually applied to analysis of small molecules, which are not able to form multiple charges, such as glycosaminoglycan (Wolff et al, 2008), polyketides (Wills et al, 2012), amino acids (Lioe & O'Hair, 2007), non-ribosomal peptide (Wills & O'Connor, 2014), small pharmaceuticals (Mosely et al, 2011;Prakash et al, 2012), ions generated from matrix-assisted laser desorption/ionization (MALDI) sources (Nielsen et al, 2003), or larger molecules like chlorophyll-a (Wei et al, 2013) or even polymeric excipients (Wei et al, 2014).…”
Section: B Other Ion-electron Reaction-based Techniquesmentioning
confidence: 99%
“…In EID, ions are irradiated with fast electrons (6-20 eV) in order to induce electronic excitation, form radical specials, and initiate dissociation. EID is usually applied to analysis of small molecules, which are not able to form multiple charges, such as glycosaminoglycan (Wolff et al, 2008), polyketides (Wills et al, 2012), amino acids (Lioe & O'Hair, 2007), non-ribosomal peptide (Wills & O'Connor, 2014), small pharmaceuticals (Mosely et al, 2011;Prakash et al, 2012), ions generated from matrix-assisted laser desorption/ionization (MALDI) sources (Nielsen et al, 2003), or larger molecules like chlorophyll-a (Wei et al, 2013) or even polymeric excipients (Wei et al, 2014).…”
Section: B Other Ion-electron Reaction-based Techniquesmentioning
confidence: 99%
“…Figure shows the results of the two-dimensional mass spectrometry analysis of TPGS performed with IRMPD and ECD as fragmentation techniques. The nomenclature for the fragmentation of TPGS is reported in this figure (top-right) as proposed in previous studies Figure a shows the 2D mass spectrum of TPGS with IRMPD as the fragmentation mode.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional analysis of the TPGS polymeric mixture in pure acetonitrile and Na 2 SO 4 with IRMPD and ECD as fragmentation techniques and proposed nomenclature . (a) IRMPD 2D mass spectrum with highlights on the most abundant fragmentations in the mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Recently, Wei et al applied CID and ECD to study the composition and structure of TPGS mixtures as well as the influence of different metal cation adducts (K + , Na + , Ag + and Li + ) on fragmentation behavior. 80 It was found that dissociation of the charge carriers from the polymer mostly depended on the binding strength and that introduction of strongly binding adducts increased the fragmentation. For ECD, the loss of adducts seemed to correlate with the metal ion's reduction potential: metals with higher reduction potential were more effective for electron capture.…”
Section: Methodsmentioning
confidence: 99%